Kinetics studies of non-isothermal melt crystallization of poly(ε-caprolactone) and poly(L-lactide) - Wanich Limwanich (2018)
© 2016, Chiang Mai Journal of Science. All Rights Reserved. The non-isothermal melt crystallization kinetics of the synthesized poly(ε-caprolactone) (PCL) and poly(L-lactide) (PLL) with identical number average molecular weight (Mn= 1.8×104) and polydispersity index (PDI = 1.8) was studied by differential scanning calorimetry (DSC). The crystallizations of PCL and PLL were performed under the cooling rates of 5.0, 7.5, 10.0 and 12.5 °C.min-1. From non-isothermal DSC analysis, the crystallization rates increased with increasing of the cooling rates, while the crystallization time decreased for both polymers. The Avrami, Ozawa and Liu models were applied to describe non-isothermal crystallization and determine kinetic parameters for PCL and PLL crystallizations. From Avrami, Ozawa and Liu models, the crystallization mechanism of PCL and PLL was nucleation with three dimensional growths. From Avrami, Liu and Friedman analysis, the synthesized PCL crystallized faster than PLL with the identical molecular weight and PDI value.